Minat Siswa SMA Negeri 4 Palu Untuk Melanjutkan Studi pada Program Studi Pendidikan Geografi Juruan Pendidikan IPS FKIP Universitas Tadulako - Samsiah, Nur; Hamid, Abdul (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This research aims to determine the interest of students at SMA Negeri 4 Palu to continue on to the Geography Education Study Program, Social Sciences Education Department, FKIP, Taadulako University. And the most important thing is the problem of what factors influence the interest of SMA Negeri 4 Palu students to continue to the Geography Education Study Program, Social Sciences Education Department, FKIP, Tadulako University. Qualitative research aims to describe what currently applies. And this research does not use hypotheses but only describes information as it is according to the variables studied. The results of the research that has been carried out can be concluded as follows: 1) The interest of SMA Negeri 4 Palu students is influenced by the element of enjoyment, willingness and attention to continue their studies in the Geography Education Study Program, Social Sciences Education Department, FKIP, Tadulako University; 2) The factors that influence students' interest in continuing their studies in the Geography Education Study Program, Social Sciences Education Department, FKIP, Tadulako University are internal factors and internal factors, namely motivation and ideals. Meanwhile, external factors are family, teachers, mass media, and the environment.